Coronavirus disease 2019 (COVID-19) in pregnancy: 2 case reports on maternal and neonatal outcomes in Yichang city, Hubei Province, China. Issue 29 (17th July 2020) - Zheng, Tingting; Guo, Jianqiang; He, Wencong; Wang, Hao; Yu, Huiling; Ye, Hong
Abstract: Rationale: The outbreak of coronavirus disease 2019 (COVID-19) in 2019 has become a global pandemic. It is not known whether the disease is associated with a higher risk of infection in pregnant women or whether intrauterine vertical transmission can occur. We report 2 cases of pregnant women diagnosed with COVID-19. Patient concerns: In all of Yichang city from January 20, 2020, to April 9, 2020, only 2 pregnant women, who were in the late stage of pregnancy, were diagnosed with COVID-19; one patient was admitted for fever with limb asthenia, and the other patient was admitted for abnormal chest computed tomography results. Diagnoses: Both pregnant women were diagnosed with COVID-19. Interventions: After the medical staff prepared for isolation and protection, the 2 pregnant women quickly underwent cesarean sections. A series of tests, such as laboratory, imaging, and SARS-CoV-2 nucleic acid examinations, were performed on the 2 women with COVID-19 and their newborns. Outcomes: One of the 2 infected pregnant women had severe COVID-19, and the other had mild disease. Both babies were delivered by cesarean section. Both of the women with COVID-19 worsened 3 to 6 days after delivery. Chest computed tomography suggested that the lesions due to SARS-CoV-2 infection increased. These women began to exhibit fever or reduced blood oxygen saturation again. One of the 2 newborns was born prematurely, and the other was born at full term. Neither infant was infected with COVID-19, but both had increased prothrombin time and fibrinogen, lactate dehydrogenase, phosphocreatine kinase, and creatine kinase isoenzyme contents. Lessons: SARS-CoV-2 infection was not found in the newborns born to the 2 pregnant women with COVID-19, but transient coagulation dysfunction and myocardial damage occurred in the 2 newborns. Effective management strategies for pregnant women with COVID-19 will help to control the outbreak of COVID-19 among pregnant women.